Analisis Peluang Usaha UMKM Makanan Tradisional di Desa Pallangga Kecamatan Pallangga Gowa - Imaduddin Imaduddin; Amirullah, Amirullah (Jurnal Masyarakat Mengabdi Nusantara, 2023)
The aim of this service is to provide guidance to the community in Pallangga Village, Pallangga District, to increase their understanding of the economic value of Micro, Small and Medium Enterprises (MSMEs), especially in the context of the traditional food "gogos". Even though they are already familiar with the use of the internet as a tool to introduce their products, this activity also explains the concept of the 4P marketing strategy (Product, Price, Place, Promotion). Special emphasis is placed on understanding that careful implementation of appropriate marketing strategies will empower people to evaluate their performance by comparing it with pre-established marketing targets. To achieve this, concrete steps in strategic marketing are prepared for each stage designed. This effort includes examples of marketing strategies for various businesses, which include SWOT analysis, such as understanding the market, formulating marketing objectives, setting the marketing mix, increasing brand awareness, and targeting mobile device users.